A proposal of smart pedagogy for the school: Educational curation as an active methodology - Santos Garcia, Marilene Santana dos; de Medeiros, Luciano Frontino (Epistemological Approaches to Digital Learning in Educational Contexts, 2020)
This chapter is a result of empirical research into methodological experiments on didactic orientations and digital fluencies to help the teacher as an educational curator. Due to the arrival of digital technologies, which generate a high value of information from a variety of sources, the educational curation of content has had to expand in recent decades from its traditional definition to a more modern one. The advent of educational curation as a smart pedagogy occurs because, from a dialogical perspective, teachers must select and organize educational, informative, and formative content with regard to the number of material and digital sources available. In return, students should be guided on how to determine what the best digital tools and resources of research are. The profile of an educational curator emerges in a scenario of pedagogical and informational needs imposed from its demands for its practices, which imply domains of diverse forms of digital influences and diversified accesses to information. The term educational curation seems to be related to the cultural universe, with its origin in the arts. However, the educational curator should apply new activities that deepen research with regard to the optimization of resources distributed by and in the digital space for his students. Thus, in addition to answering these questions, this chapter is available for the educational curator, who proposes critical thinking, fake-news analysis, and creative activities through active and smart methodologies that can be applied in a school. This chapter intends to expand on the definition of educational curation, and what we can understand from the theoretical-practical perspective of active methodologies. It shows some orientations about its abilities, competences, and digital fluencies as a result of the empirical research of methodological experiments. Lorenzo and Gallon understand that the current moment is aimed at a new pedagogy, but this should not mean offering technologies that present the knowledge of society, but instead seek to engage the students in their learning with different practices in search of knowledge. The educational curator should practice having more engaging dialogues with students and other fellow teachers while working within the school context. The educational curator is an organizer of content focused on research and research that uses the choices and involvement of students. He uses logical reasoning, and, at the same time, is also sensitive and intuitive.